A Biblioteca escolar como incentivadora da educação ambiental - RABELO, Fabiane do Socorro Lopes (2019)
Presents the educational mission of the school library, points out the possibility of the librarian as an educator and discusses environmental issues, making the historical context of the 1960s to the 2030 agenda for sustainable development. The objective is to point out the importance of the school library for the development of projects that encourage environmental education. The methodology used was documented (printed and electronic). The research is qualitative and quantitative. The results point out that the school library is indispensable for the educational process, when it works in conjunction with the school it can encourage environmental education through the elaboration of projects and events that address this theme, it should be directed by a proactive librarian, who embraces the side social science of librarianship and transform the library into an active and dynamic space, thus contributing to the creation of critical thinking in children and adolescents about environmental issues.